THE EFFECTIVENESS OF USING AUDIO-VISUAL MEDIA BASED ON POLYA'S PROBLEM-SOLVING THEORY IN ELEMENTARY SCHOOL STUDENTS' MATHEMATICS LEARNING (CASE STUDY AT THE UPTD SDN MAULAFA) - Khatrin Taku Neno (Journal of Innovative Technologies in Learning and Education, 2026)
This study aimed to examine the effectiveness of using audio-visual media based on Polya’s Problem-Solving Theory in improving elementary school students’ mathematical problem-solving abilities. This research employed a quantitative approach with a quasi-experimental design using a pretest–posttest control group design. The subjects of the study were elementary school students at UPTD SDN Maulafa, who were divided into an experimental group and a control group. The experimental group was taught using audio-visual media integrated with Polya’s problem-solving stages, while the control group received conventional instruction. Data were collected through problem-solving tests and classroom observations. The data were analyzed using descriptive statistics and inferential statistics, including normality tests, homogeneity tests, and independent samples t-tests. The results showed that students in the experimental group achieved higher posttest scores and greater improvement in mathematical problem-solving abilities compared to students in the control group. Statistical analysis indicated that the data were normally distributed and homogeneous, and the t-test results revealed a significant difference between the two groups. Observation results also showed that students in the experimental group demonstrated higher levels of engagement, participation, and motivation during the learning process. Based on these findings, it can be concluded that the use of audio-visual media based on Polya’s Problem-Solving Theory is effective in improving elementary school students’ mathematical problem-solving abilities and learning activities. This instructional approach can be considered an effective and innovative alternative for enhancing the quality of mathematics learning in elementary schools.